การศึึกษาแนวทางการปฏิบัติของโคบิต (COBIT) ในการนำโอเพนซอร์สมาใช้ในองค์กร กรณีศึกษาบริษัท ไอซีที ที่จัดตั้งเพื่อบริษัทในเครือ - อรุณธารี สันติพงศ์ (Journal of Food Health and Bioenvironmental Science, 2013)
Abstract This research was aimed to study an approach for adoption and implementation of the Open Source Software (OSS) within the organization of the ICT Company. This was because the high level executives of the organization realized the benefits of reduction of the risks from illegally using copyright software and cost reduction on software license which had been greatly increased, with the aim to use the software as a tool in negotiation for reduction of license cost with service providers such as Microsoft Corporation and Oracle Corporation. Consequently, the Research and Development (R&D) Unit was assigned to study and experiment with the adoption and implementation of OSS, by experimenting with personal computers and the computer system at the division level of the organization in order to replace the closed source software system or proprietary license software system. However, the study and implementation at the organizational level was not easy because the work team had to face problems and obstacles, such as, the technical and compatibility with the old data problems, and the operational skills and familiarity habits of the end-users. The ICT Company Limited was a company that operated as the IT Division of the subsidiary companies in the group. Due to the diversity of the work systems and the difference of information technology architectural structures of the subsidiary companies in the group and the lack of the groupûs own information technology architectural structure, if an organization, especially the one that operated in the similar business as that of the ICT Company Limited wanted to select and develop OSS to implement in the organization, such an implementation would certainly affect the main information technology architectural structures of the main subsidiary companies. For this reason, the researcher decided to study the application of the Control Objective for Information and Related Technology (COBIT) framework, which was a driving tool for every organization to practice good IT governance, as the model for evaluation and analysis of the IT process for the OSS adoption in order to improve it to be in accordance with the programs of the organization. Such an application required that the personnel in the work unit assigned to develop the systems must follow the COBIT framework in all four main procedures, namely, (1) planning and organization, (2) acquisition and implementation, (3) delivery and support, and (4) monitoring. The procedures were to be applied with the six main factors which were the main characteristics of OSS comprising (1) strategy, (2) external support, (3) cost consideration, (4) skilled IT staff, (5) training of users, and (6) implementation. From this case study, the researcher could conclude the results of analysis of the model and interviews of all concerned personnel that throughout the past and up to the present, the R&D Unit still could not deliver the work to the Service Delivery (SD) Division, which functioned on ITC service provision including work performance techniques and maintenance of the application system, because the company still did not have a clear program based on the organizational administration and management. For example, the researcher found that the organization still lacked the analysis and study of the trend of the technology to be adopted, still had not determined an OSS strategic plan in the organization, still had no clear assignment for joint responsibility of the personnel in the organization, and still lacked the clear resource allocation for the sufficient capital and qualified personnel to support and maintain the system. However, if the organization could apply the COBIT framework to support the IT technology strategic planning of the organization from the beginning, it would enable the organization to know the required personnel resource, project budget, and the clear participation of every member in the organization, resulting in the successful development of OSS for implementation within the organization. The project would be efficient and could reduce software license cost of the organization. Keywords : Proprietary Licensed, Unlicensed, Free/Open Source Licensed, IT Governance, Control Objective for Information and Related Technology